ASYMMETRIC SLOT LINES FOR CREATING MILLIMETER-WAVE SEMICONDUCTOR COMPONENTS - Karushkin, M.; Rukyn, V. (Radio physics and radio astronomy (Print), 2025)
Subject and Purpose. Creating hybrid-integrated semiconductor components in the millimeter wave range implies simplified manufacturing technology and reduced labor intensity. At the same time, these components offer the potential for improved electrical parameters compared to the waveguide counterparts. The article aims to explore methods for creating millimeter-wave devices using a waveguide asymmetric slot line combined with an asymmetric stripline accommodating active semiconductor structures. Methods and Methodology. The development of millimeter-wave hybrid-integrated semiconductor active components upon transistors, avalanche diodes, and p–i–n diodes is considered. An asymmetric slot line (ASL) is used as a transmission line installed in the E-plane of a regular waveguide. The ASL base material is a low-loss dielectric stuff RT/duroid 5880 with dielectric constant ε = 2.2. The semiconductor elements are bonded to a short section of an asymmetric stripline fabricated by partial metallization of an asymmetric corner line. The insertion of a low-impedance asymmetric stripline section equipped with a heat sink allows efficient active semiconductor microwave components of continuous-wave and pulse modes. This design also supports high-speed switching devices of a wide frequency band of operation. Results. Directing away large heat fluxes generated during the operation of the active elements is a growing challenge in developing and making millimeter-wave semiconductor components. The paper provides examples of the efficient microwave power level increase by reducing the operating temperature of the components. Extended-geometry active components (IM- PATT diodes) also serve the purpose. These methods enabled us to increase the output power of the microwave devices by 40 to 50%, the temperature of the p-n junction of the active element therewith was not increasing. This allows microwave power amplifiers to be built around semiconductor distributed-parameter structures like narrow, wavelength-comparable strips. Conclusion. The authors’ developments have been presented against the background of contemporary information on the current state and progress in the creation of millimeter-wave components of hybrid-integrated design.